The Delusional Character, Alfred, during the War in Ruta Sepetys’ Salt to the Sea - Nurhayati Purba; Fransisca Theresia; Pahotan Sinaga; Anna Riana Suryanti Tambunan (Journal of English Language Studies, 2023)
This research aims the delusion within Alfred, the main character in Ruta Sepetys’ Salt to the Sea. The delusion within the main character has great impact toward the novel. Ritunanno and Bortolotti’s (2021) theory of delusion is meant to analyze the delusion within the main character.  This method is adequate for analyzing the delusion within the main character in Salt to the Sea novel. This research uses qualitative method. The data will be taken from dialogues between the main character with other characters and the author’s narrations. The delusion within the main characters is collected by identifying and classifying the dialogues into the beginning, the process, and the result of the delusion within the main character. The delusion is portrayed by Alfred which leads to the tragic impacts. The beginning of the delusion occurs in Alfred’s environments that depicts how his parents and friends treat him in certain ways he does not want to. While, the process of the delusion occurs when he’s on duty during the war. It is interpreted how he goes through such underestimation toward colleagues and strangers being rude to him. Eventually, the impacts make some significant changes toward Alfred’s character. The positive impacts are the remembrance of his mother and the details of the ship. And the negative impacts are the neglect on other people and his death. All in all, this research shows the worst that the delusion could create to Alfred is his death.